2011
DOI: 10.1001/archneurol.2011.127
|View full text |Cite
|
Sign up to set email alerts
|

A Benign Form of Neuromyelitis Optica

Abstract: Background: Few data exist on a possible benign form of neuromyelitis optica (NMO).Objectives: To identify NMO with a good outcome (go-NMO) among a large population of patients and to describe demographic and clinical variables associated with go-NMO vs standard NMO and benign multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 26 publications
1
35
1
Order By: Relevance
“…The timing of MRI in the evolution of NMOSD also may influence the length of the imaged lesion; 18 early imaging may miss a long lesion 11 and late imaging may reveal a discontinuous or short lesion, or no lesion. 18, 20 The interval from symptom onset to MRI did not differ significantly for patients with LETM or STM; imaging was performed within 90 days of symptom onset in all patients, and lesional activity was confirmed by gadolinium enhancement in 56% of seropositive STM episodes. In AQP4-IgG positive NMOSD patients evaluated at the time of STM attack, the severity of myelitis at nadir was milder than those with LETM.…”
Section: Discussionmentioning
confidence: 95%
“…The timing of MRI in the evolution of NMOSD also may influence the length of the imaged lesion; 18 early imaging may miss a long lesion 11 and late imaging may reveal a discontinuous or short lesion, or no lesion. 18, 20 The interval from symptom onset to MRI did not differ significantly for patients with LETM or STM; imaging was performed within 90 days of symptom onset in all patients, and lesional activity was confirmed by gadolinium enhancement in 56% of seropositive STM episodes. In AQP4-IgG positive NMOSD patients evaluated at the time of STM attack, the severity of myelitis at nadir was milder than those with LETM.…”
Section: Discussionmentioning
confidence: 95%
“…In the current study, VA results were similar to that of previous studies; however, visual recovery during the remission period at the first ON attack was not significantly different between groups. Recent studies have found that a substantial number of NMO cases are usually associated with mild symptoms or a benign long-term course [33,34]; therefore, the outcome of a single isolated ON case cannot be determined according to VA recovery at first onset.…”
Section: Discussionmentioning
confidence: 99%
“…This is based on two principles: first, that there is no ‘benign’ NMO 81. Second, if AQP4-antibodies are present, then relapses are invariable at some point.…”
Section: Treating Nmosdmentioning
confidence: 99%